2001
DOI: 10.1074/jbc.m004788200
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Bifunctional Escherichia coli N-Acetylglucosamine-1-phosphate Uridyltransferase Enzyme into Autonomously Functional Domains and Evidence That Trimerization Is Absolutely Required for Glucosamine-1-phosphate Acetyltransferase Activity and Cell Growth

Abstract: The bifunctional N-acetylglucosamine-1-phosphate uridyltransferase (GlmU) enzyme catalyzes both the acetylation of glucosamine 1-phosphate and the uridylation of N-acetylglucosamine 1-phosphate, two subsequent steps in the pathway for UDP-N-acetylglucosamine synthesis in bacteria. In our previous work describing its initial characterization in Escherichia coli, we proposed that the 456-amino acid (50.1 kDa) protein might possess separate uridyltransferase (N-terminal) and acetyltransferase (C-terminal) domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 35 publications
3
32
0
1
Order By: Relevance
“…In this context, the presence of large inserts in essential enzymes involved in cell wall synthesis has the potential to inactivate or modify the cellular functions of such proteins. It should be pointed out in this regard, that GlmU is a bifunctional protein which catalyses two of the essential steps leading to the synthesis of UDP-N-acetylglucosamine, a fundamental precursor for bacterial cell wall synthesis (Gehring et al, 1996 ;Pompeo et al, 2001). It has been shown that the N-terminal domain of this protein (residues 3-227 in E. coli) catalyses the uridyltransferase activity whereas the C-terminal domain is responsible for the acetyltransferase activity (Brown et al, 1999 ;Pompeo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the presence of large inserts in essential enzymes involved in cell wall synthesis has the potential to inactivate or modify the cellular functions of such proteins. It should be pointed out in this regard, that GlmU is a bifunctional protein which catalyses two of the essential steps leading to the synthesis of UDP-N-acetylglucosamine, a fundamental precursor for bacterial cell wall synthesis (Gehring et al, 1996 ;Pompeo et al, 2001). It has been shown that the N-terminal domain of this protein (residues 3-227 in E. coli) catalyses the uridyltransferase activity whereas the C-terminal domain is responsible for the acetyltransferase activity (Brown et al, 1999 ;Pompeo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the protein UDP-N-acetylglucosamine pyrophosphorylase (GlmU), which catalyses both the acetylation of glucosamine 1-phosphate and the uridylation of N-acetylglucosamine 1-phosphate to produce UDP-N-acetylglucosamine (Gehring et al, 1996 ;Pompeo et al, 2001), a 17 aa indel in a conserved region has been identified that is commonly shared by various archaea and chlamydial species (Fig. 3).…”
Section: Horizontal Transfer Of a Cell Wall Biosynthesis Gene (Glmu )mentioning
confidence: 99%
“…It was demonstrated that the acetyltransferase activity of the full-length protein is suppressed when embedded within heterotrimers produced in the presence of the truncated protein; thus, suggesting that the enzymatic activity necessitates a trimeric organization, with the catalytic site involved in contact sites between adjacent monomers. It was demonstrated that trimerization was perspicuously necessary for glucosamine-1-phosphateacetyltransferase activity and cell growth [14].…”
Section: Mechanisms In Proteincarbohydrate Interactionsmentioning
confidence: 99%
“…N-acetylglucosamine-1-phosphate uridyltransferase (Gimu) exhibits the properties of a bifunctional enzyme that catalyses both the acetylation of glucosamine 1-phosphate and uridylation of N-acetylglucosamine 1-phosphate, as well as two concomitant levels in the UDP-N-acetylglucosamine synthesis pathway in bacteria [14]. It is proposed that the 456-amino acid (50.1kDa) protein may contain disparate uridyltransferase (N-terminal) and acetyltransferase (C-terminal) domains; which is confirmed via expression of the two distinct folding and functional domains.…”
Section: Mechanisms In Proteincarbohydrate Interactionsmentioning
confidence: 99%
“…The two enzymatic activities are contained within two distinct domains of the GlmU protein and are independent of each other. 3,4 The acetyl transferase activity is carried out by the C-terminal domain, which adopts a trimeric left-handed parallel beta helix (LbH) fold. 5,6 The uridyl transferase activity is contained within the globular N-terminal domain, which is part of the nucleotide triphosphate transferase superfamily of enzymes that resemble the Rossman fold and require magnesium for catalysis.…”
Section: Introductionmentioning
confidence: 99%